(untitled) (Scientific journal of the Fergana State University, 2023)
The article reflects semantic, pragmatic or rhetorical discourse functions related in many ways to the interactional and socio-cultural functions. They always require a socio-cognitive interface, that is, episodic models of specific socio-cultural events and shared general knowledge or attitudes about societal structures, which both can be mapped on or constrain the cognitive representations that underlie a specific discourse.